Gendered Emotional Expression in Star Wars : Episode IV Soundtrack - Sutinen, Saana (2020)
Entertainment does not only portray reality but also constructs it by influencing the culture around it. Thus, knowledge of the mechanisms with which this happens in music and in multimedia can be seen as a part of media literacy, which in turns needs multidisciplinary research to produce knowledge of those mechanisms. The aim of this work is to draw from multiple different fields, such as music analysis, music and emotion research, and gender and emotion research, to answer the following questions: How does emotional expression get constructed in the structure of music in a film music context? How do those musical expressions of emotion construct gender when music is linked to a certain character? How is the music of the first Star Wars film, Episode IV: A New Hope, constructing the gender of the characters linked to the music via gendered emotional expression and beyond gendered associations of instruments? The analysis concerned the following features: articulation, loudness, pitch, harmony and tonality, and tempo. A major part of the extraction of musical features was done with the assistance of MIRtoolbox, a Matlab toolbox for Music Information Retrieval. In this way, specific information and numeral values as well as visual output for the features could be obtained without the need to transcribe the whole orchestral score. The MIRtoolbox output was then compared to source material on emotional expression in music, and emotion words were assigned for the tracks. Finally, those emotion words were considered in relation to source material on gendered emotional expression. The results show that there are systematic differences in the emotional expression between tracks linked to characters of different genders. Particularly in the cases of the features of loudness and articulation, tracks linked to female protagonist Princess Leia were found to portray less active and more inwards directed emotions compared to the other tracks or tracks linked to male protagonist Luke Skywalker. Better awareness of the mechanisms behind differences in emotional expression in music and their gendering qualities can be gained by systematically studying the different features of the music beyond the level of listener experience. Further research is needed to develop understanding on how or if this can be seen in other films, in other genres of film and music and in music by other composers. Additionally, other musical features can be included.